PAPR Reduction in OFDM Systems using Partial Transmit Sequence combined with Cuckoo Search Optimization Algorithm (ICAT16-0286) - BOZKURT, YÃƒÂ¼ksel TOKUR; TASPINAR, Necmi (International Journal of Intelligent Systems and Applications in Engineering, 2016)
Partial transmit sequence (PTS) scheme is one of the efficacious tool for lessening peak-to-average power ratio (PAPR) in orthogonal frequency division multiplexing (OFDM) system. However, computational cost for the optimum phase factors searches of PTS scheme entails huge computational requirements and limits its applicability to practical applications especially for high-speed data transmissions. This study proposes a PAPR reduction method with a low computational complexity based on a combination of cuckoo search optimization algorithm with PTS scheme in OFDM system. In terms of PAPR and computational cost reductions, the performance of the cuckoo-PTS scheme is comparatively investigated by performing a set of simulations with different PTS schemes.